Amended Safety Assessment of Chamomilla recutita-Derived Ingredients as Used in Cosmetics. (November 2018) - Johnson, Wilbur; Boyer, Ivan; Bergfeld, Wilma F.; Belsito, Donald V.; Hill, Ronald A.; Klaassen, Curtis D.; Liebler, Daniel C.; Marks, James G.; Shank, Ronald C.; Slaga, Thomas J.; Snyder, Paul W.; Gill, Lillian J.; et al.
The Chamomilla recutita -derived ingredients in this assessment are reported to function mostly as fragrance ingredients and skin conditioning agents in cosmetic products. Because final product formulations may contain multiple botanicals, each containing the same constituents of concern, formulators are advised to be aware of these constituents and to avoid reaching levels that may be hazardous to consumers. Additionally, industry should continue to use good manufacturing practices to limit impurities that could be present in botanical ingredients. The Cosmetic Ingredient Review Expert Panel concluded that the Chamomilla recutita -derived ingredients are safe in cosmetics in the present practices of use and concentration described in the safety assessment when formulated to be nonsensitizing.